If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 6 = 4x + 4 Reorder the terms: 6 + 6x = 4x + 4 Reorder the terms: 6 + 6x = 4 + 4x Solving 6 + 6x = 4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + 6x + -4x = 4 + 4x + -4x Combine like terms: 6x + -4x = 2x 6 + 2x = 4 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + 2x = 4 + 0 6 + 2x = 4 Add '-6' to each side of the equation. 6 + -6 + 2x = 4 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 4 + -6 2x = 4 + -6 Combine like terms: 4 + -6 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| u+4=12 | | (.66x+x)*2=220 | | 7-12=5 | | -2=x-12 | | 7+3k-12=25 | | 7-12= | | 3x^2-15= | | 7-12/3*4= | | 0.14(y-9)+0.10y=0.04y-0.01(60) | | 60k+80=50k+120 | | 10(6)= | | 7-(-60)= | | 6-5(2m-3)=-29 | | -6(2x-3)+15=19 | | 2.5t+6=10t+24 | | (2x+5)=-2 | | 2x-(3y-(4x-(5y-(6x-7y))))= | | 6g+20=2g+36 | | 4y+19=2y+10 | | 2x+3-5(x+1)=6x+5 | | 180=2x+(x+10)+(2x-30) | | [x]=10 | | 3-5(7y-11)= | | 0.14(y-9)+0.10=0.04y-0.01(60) | | x+189326=12 | | 6x^2=-24 | | -4(3x-1.5)+7=39 | | 50+(2x-4)=90 | | -1(x-9)+4x= | | 10-5x=55 | | 0.7(3.90-9x)=5.6x | | 3x-36+7=7 |